Implementasi Peraturan Nomor 50 Tahun 2017 Tentang Disiplin Pegawai Negeri Sipil Di Sekretariat Daerah Kabupaten Batu Bara - Sri Mahdani; Siti Mardiana; Nina Siti Salmaniah Siregar (Universitas Medan Area, 2022)
The purpose of the study was to analyze the implementation, obstacles and efforts to implement the Regent's Regulation Number 50 of 2017 concerning Civil Servant Discipline at the Regional Secretariat of Batu Bara Regency. The method used in this research is a qualitative method, which is a research method used to conduct research naturally using various available methods. The results showed that from an organizational perspective the implementation of work discipline was not optimal, where there was a lack of understanding of human resources, namely a head of service and other SKPD in the implementation of the organizational structure and lack of ability to carry out good performance in accordance with the organizational structure. In terms of interpretation of the implementation of work discipline, a head of service should be able to socialize technical instructions and implementation instructions on work discipline ranging from electronic attendance, morning apples and work hours, but the reality is that a head of service does not have seriousness in creating good communication with ASN so that technical instructions and instructions for implementing work discipline have not run optimally within the Regional Secretariat of Batu Bara Regency. In terms of implementation, the Regional Head gives sanctions to officials who have problems in their inability to improve work discipline so that the head of the service is not given a job or is not given another position at the Regional Secretariat of Batu Bara Regency due to disharmony between the head of the service who has problems with the Regional Head.